Gram-negative bacteria as causative agents of ventilator-associated pneumonia and their respective resistance mechanisms. (2nd October 2020) - Bandić-Pavlović, Daniela; Zah-Bogović, Tajana; Žižek, Marta; Bielen, Luka; Bratić, Vesna; Hrabač, Pero; Slačanac, Domagoj; Mihaljević, Slobodan; Bedenić, Branka
Abstract: Ventilator-associated pneumonia (VAP) is a serious and common complication in patients admitted to intensive care unit (ICU) and contributes to mortality. Multidrug Gram-negative bacteria such as Acinetobacter baumannii, Pseudomonas aeruginosa, and Klebsiella pneumoniae are frequently associated with VAP in ICU. A prospective study was set up in three ICUs of the University Hospital Center Zagreb and one ICU in General Hospital Pula from September 2017 to March 2018. Antibiotic susceptibility was determined by broth microdilution method. Production of extended-spectrum β-lactamases (ESBLs) was determined by double-disk synergy test and carbapenemases by Hodge and carbapenem inactivation method (CIM). The genes encoding ESBLs, carbapenemases of class A, B and D and qnr genes were determined by PCR. In total 97 Gram-negative bacteria isolates were analyzed. P. aeruginosa demonstrated high resistance rates for imipenem and meropenem with 74% and 68% of resistant strains, respectively. Moderate resistance rates were observed for ceftazidime andpiperacillin/tazobactam, ciprofloxacin and gentamicin (44%). All except three A. baumannii isolates, were resistant to carbapenems and to all other antibiotics apart from colistin and amikacin. Eight A. baumannii isolates were positive for bla OXA-23 and 12 for bla OXA-24 genes. Four K. pneumoniae and two E. cloacae strains were ESBL positive and harboured group 1 of CTX-M β-lactamases. Three P. mirabilis strains were positive for plasmid-mediated ampC β-lactamase of CMY family. Two carbapenem-resistant K. pneumoniae harboured OXA-48 and one carbapenem-resistant E. cloacae VIM-1. A high proportion of multidrug-resistant P. aeruginosa, K. pneumoniae and extensively resistant A. baumannii was reported. Acquired resistance mechanisms, mainly production of carbapenemases and ESBLs were dominant in A. baumannii and K. pneumoniae, respectively. Resistance of P. aeruginosa isolates was more likely due to upregulation of efflux pumps or porin loss. A marked diversity of β-lactamases was identified in Enterobacteriaceae .